The effects of an activation-dependent increase in titin stiffness on whole muscle properties using finite element modeling - Cankaya, A. O.; Pamuk, U.; Yucesoy, C. A. (Journal of Biomechanics, 2021)
Active state titin`s effects have been studied predominantly in sarcomere or muscle fiber segment level and an understanding of its functional effects in the context of a whole muscle, and the mechanism of those is lacking. By representing experimentally observed calcium induced stiffening and actin-titin interaction induced reduced free spring length effects of active state titin in our linked fiber-matrix mesh finite element model, our aim was to study the mechanism of effects and particularly to determine the functionally more effective active state titin model. Isolated EDL muscle of the rat was modeled and three cases were studied: passive state titin (no change in titin constitutive equation in the active state), active state titin-I (constitutive equation involves a higher stiffness in the active state) and active state titin-II (constitutive equation also involves a strain shift coefficient accounting for titin`s reduced free spring length). Isometric muscle lengthening was imposed (initial to long length, lm = 28.7 mm to 32.7 mm). Compared to passive state titin, (i) active state titin-I and II elevates muscle total (lm = 32.7 mm: 14% and 29%, respectively) and active (lm = 32.7 mm: 37.5% and 77.4%, respectively) forces, (ii) active state titin-II also shifts muscle`s optimum length to a longer length (lm = 29.6 mm), (iii) active state titin-I and II limits sarcomere shortening (lm = 32.7 mm: up to 10% and 20%, respectively). Such shorter sarcomere effect characterizes active state titin`s mechanism of effects. These effects become more pronounced and functionally more effective if not only calcium induced stiffening but also a reduced free spring length of titin is accounted for.